Banality of Privilege: Examining Why EDI Is Under Assault Through the Case of the Ontario Equity Policy - Ibrahim, Awad; Boivin, Nettie (Canadian Journal of Education/Revue canadienne de l’éducation, 2026)
Grounded in extensive interviews with teachers and school-level administrators in Ontario, Canada, this article proposes banality of privilege as a primary reason for why EDI has turned into a performative act, which facilitated its attack. To make banality of privilege concrete, we suggested three forces and six tenets that helped us in our data analysis. Collected through interviews with teachers and school administrators between 2024–2025, the data show that embedded institutional barriers are the frontline of all issues that hinder effective communication, implementation, and administration of EDI policy; and that, among these barriers, the primary obstacle to a meaningful EDI implementation is not financial constraint, but a systemic lack of buy-in or interest convergence, specifically at the leadership level. This lack of buy-in from leadership, we show, trickles down to staff and the broader school community, resulting in low engagement and missed opportunities for meaningful inclusion. This not only renders EDI performative, but it gives reasons for why it is under attack. For those of us who are working toward a just world, we conclude, we need to be mindful of this situation and address the concerns of the EDI critics.